2006
DOI: 10.1159/000090132
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Urocortin Has Potent Antioxidative Properties and Is Upregulated by Inflammatory Cytokines and Pitavastatin

Abstract: Background: Urocortin, a neuropeptide discovered in the midbrain, is a member of the corticotropin-releasing factor family and is expressed in heart tissues. Urocortin exerts potent cardioprotective effects under various pathological conditions including ischemia/reperfusion. However, the regulation and function of vascular urocortin are unknown. Methods and Results: Immunohistochemistry showed definitive expression of urocortin in endothelial cells of coronary large arteries and microvessels from autopsied he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 59 publications
(43 reference statements)
1
41
1
1
Order By: Relevance
“…For instance, it was shown that proinflammatory cytokines, such as TNFα and IFNγ, upregulated UCN1 protein expression in human umbilical vein endothelial cells, while UCN1 effectively attenuated the generation of ROS induced by Ang II [103]. In another study, it was found that UCN1 suppressed the LPSinduced upregulation of MCP1 and ICAM1 in human endothelial cells [100].…”
Section: Urocortinmentioning
confidence: 99%
“…For instance, it was shown that proinflammatory cytokines, such as TNFα and IFNγ, upregulated UCN1 protein expression in human umbilical vein endothelial cells, while UCN1 effectively attenuated the generation of ROS induced by Ang II [103]. In another study, it was found that UCN1 suppressed the LPSinduced upregulation of MCP1 and ICAM1 in human endothelial cells [100].…”
Section: Urocortinmentioning
confidence: 99%
“…In addition, one study showed that pitavastatindirectlyinhibitstheformationofROSin endothelialcells 118) .Therefore,individualstatinsexert distinct antioxidant effects via diverse mechanisms and/ortheiractionsinvariouscellsystems.…”
Section: Role Of the Antioxidant And Anti-inflammatory Effects Of Stamentioning
confidence: 99%
“…These findings suggest that Ucn I and its related peptides may be regulated by inflammatory cytokines, such as LPS and TNF-a, and may play a pathophysiological role in the diseased heart because CRH-R2 signaling in the heart may be very important for adaptation to cardiac stress in pathological conditions (Coste et al 2000). Ucn I may be regulated in response to oxidative stress, thereby exerting a vasoprotective role against the oxidative stress caused by angiotensin II (Ang II) in HUVECs (Honjo et al 2006). We hypothesized that Ucn I and its related peptides may be regulated by inflammatory and/or oxidative stress(es) in the diseased heart.…”
Section: Introductionmentioning
confidence: 99%
“…Urocortin (murine urocortin: Ucn, human urocortin: UCN) I, Ucn II, and Ucn III, the members of corticotropin-releasing hormone (CRH)-related peptides, have various actions on the cardiovascular system via cAMP-dependent pathways and the extracellularly regulated kinase 1/2 pathway (Ikeda et al 1998, 2002, 2005a, Brar et al 2004a, Honjo et al 2006. We previously reported the pathophysiological involvement of UCN I in cardiomyopathies (Ikeda et al 2003), in which a patient's plasma concentration of tumor necrosis factor (TNF)-a increased (Matsumori et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation